Determination of Heavy Metal Concentrations on some Selected Herbal Medicinal Preparations Marketed in Kano State, Nigeria - Zigau, Z. A.; Aliyu, B. S.; Abubakar, U. S.; Bello, A. A.; Yakasai, M. A.; Sanusi, H. (UMYU Journal of Microbiology Research)
Study’s Novelty/Excerpt